Behavior of elliptical buckling-restrained braces under cyclic axial load. (February 2023) - Zhou, Yun; Shao, Hetian; Lui, Eric M.; Zhong, Genquan; Li, Zhuang
Abstract: An experimental and numerical study of a novel buckling-restrained brace made from elliptical steel tube with a dog bone shaped core plate (CEST-DBRB) is presented. Two CEST-DBRB specimens with major-to-minor axis ratios of 1.6 and 2.0 are tested under a displacement controlled cyclic load protocol. The test results show that both specimens exhibit stable hysteretic behavior without experiencing overall buckling. However, local bulging of the steel tube occurs under large displacement amplitudes. Using ABAQUS, finite element models are developed to analyze these BRBs and to study how stress concentrations contribute to local instability. Upon comparison with a BRB with circular cross-section, it is shown that these elliptical BRBs exhibit comparable hysteretic behavior, despite being 30%-40% lighter in weight and smaller in volume. A criterion to prevent steel tube bulging is established and an equation to calculate the lateral force exerted on the restraining unit by the core plate is proposed.